Diagnostic and failure analysis in blades of a 300 MW steam turbine. (December 2017) - Segura, J.A.; Castro, L.; Rosales, I.; Rodriguez, J.A.; Urquiza, G.; Rodriguez, J.M.
Abstract: A steam turbine from a thermoelectric central was put into maintenance due to a forced outage for high vibrations. Visual inspection of the steam turbine of 300 MW showed blades fractured at the last stage, L-0 and these affected other blades. Some operating parameters demonstrated to be out of range such as flow steam, low vacuum, and several areas in blade result to be damaged by the implosions particle. Three blades were fractured and others with a considerable crack presence were detected. The damage and fracture in the blades joints are attributed to high vibrations stresses combined with high cycle fatigue. A metallographic study revealed that the fracture was initiated from a cavity due to particle erosion. Numerical calculation results have shown that stubs blades group are disconnected as a result of the firstly vibratory stresses during startup and shutdown of the turbine. Resonance phenomena are present in the first blade when this is a detachment of the group initializing a crack propagation process. Number cycles before crack propagation in the blades of the last stage of a steam turbine of 300 MW were calculated. Highlights: Vibration stresses produce cracks in blades joints. Resonance induces high stresses in blades group causing failures in the steam turbine. Fracture initiate from a cavity due to erosion.